2000
DOI: 10.1001/archopht.118.10.1401
|View full text |Cite
|
Sign up to set email alerts
|

Argatroban Inhibits Intraocular Fibrin Formation After Vitrectomy in Rabbits

Abstract: Objectives: To examine whether the specific thrombin inhibitor argatroban can prevent anterior chamber, pupillary area, and anterior vitreous fibrin formation after vitrectomy and lensectomy in rabbits. Methods: Argatroban was infused into the vitreous cavities of Japanese albino rabbits for 5 minutes after pars plana vitrectomy and lensectomy. Slitlamp microscopy and indirect ophthalmoscopy were performed at postoperative hours 0.5, 1, 2, 3, and 6, and at postoperative days 1, 2, 3, and 7, and the amounts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…It is known that PARs transmit proinflammatory signals including the expression of inflammatory and growth factors, 44 and that anticoagulant therapy attenuates inflammatory responses and fibrin formation in the retina. [45][46][47] It is suggested that the therapeutic action of triamcinolone in retinal edema and neovascularization is mediated in part by the inhibitory effect on the action of thrombin. Thrombin is used as a therapeutic agent, for example, for the closure of macular holes 48 ; this effect of thrombin may be mediated by the autocrine/paracrine mitogenic 21,22 and motogenic action of PDGF (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that PARs transmit proinflammatory signals including the expression of inflammatory and growth factors, 44 and that anticoagulant therapy attenuates inflammatory responses and fibrin formation in the retina. [45][46][47] It is suggested that the therapeutic action of triamcinolone in retinal edema and neovascularization is mediated in part by the inhibitory effect on the action of thrombin. Thrombin is used as a therapeutic agent, for example, for the closure of macular holes 48 ; this effect of thrombin may be mediated by the autocrine/paracrine mitogenic 21,22 and motogenic action of PDGF (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…31 Maeno et al proposed the more specific inhibitor Argatroban. 32 If prevention fails to be effective and an RPM forms, AlphaCor data suggest that if detected early the membrane may respond well to Nd:Yag and topical steroid therapy. Possible damage to PMMA KPro optics by Nd:Yag was suggested following in vitro studies 33 but appears not to be a problem clinically with PMMA-optic devices.…”
Section: Discussionmentioning
confidence: 99%
“…The drugs half-life is 30 min, and it has an anticoagulant effect for about 15 min after administration. Therefore, by stopping argatroban as soon as the dissection of the fibrovascular membranes is completed, there is little risk of postoperative bleeding and clotting can be safely controlled [ 13 ]. A worsening of PDR with increased platelet aggregation has also been reported [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%